Strategies to meet marital intimacy needs in women infected with coronavirus 2019: A framework qualitative content analysis research - Tahmineh Farajkhoda; Mahmood Kamali Zarch; Saeedeh Najafihedeshi (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Separating women with the coronavirus 2019 from family can affect marital life. Considering psychological vulnerability of women for anxiety and depression disorders, these women may experience more stress due to the loss of work at this time or special reproductive health conditions such as pregnancy, having a baby, or other medical conditions. Objective: Considering a limited number of qualitative studies on the need for marital intimacy, this study was conducted to meet marital intimacy needs in women with coronavirus 2019. Materials and Methods: Framework qualitative content analysis was conducted through participation of 13 key informants (sex therapist, couple therapist, psychologist, and midwifery counselor) and 18 infected women from Yazd, Iran in July 2020 who were selected purposefully and interviewed through the semi-structured in-depth interviews. Results: 3 main categories were: 1) mutual resilience (subcategories: 1. coping strategies; 2. value of marital life; 3. compassionate conflict resolving). 2) skillful relationship (subcategories: 1. assertiveness in sexual expression; 2. self-efficacy in the distance physical connectivity). 3) synergy (subcategories: 1. reframing spirituality closeness; 2. empowering aesthetic creativity; 3. management of family function, and 4. prioritizing). Conclusion: Findings revealed sex and couple therapists, health providers, and policymakers should emphasize on using new forms of digital communication in these couples. Teaching skills that increase partners' creativity and empathy, enable women to fulfill their mental, sexual and reproductive health needs, and lead to more partners responsibility and loyalty, and maintenance of family function. In times of crisis, counseling should be considered in women treatment programs and care guidelines.